2022
DOI: 10.1155/2022/5694223
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Alleviates Muscle Atrophy Caused by Oxidative Stress Induced by Cisplatin through ERK/FoxO and JNK/FoxO Pathways

Abstract: Cisplatin (DDP), a widely used chemotherapeutic drug in cancer treatment, causes oxidative stress, resulting in cancer cachexia and skeletal muscle atrophy. This study investigated the effects and activity of silibinin (SLI) in reducing DDP-induced oxidative stress and skeletal muscle atrophy in vivo and in vitro. SLI alleviated weight loss, food intake, muscle wasting, adipose tissue depletion, and organ weight reduction induced by DDP and improved the reduction of grip force caused by DDP. SLI can attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Moreover, alleviated grip strength and the myofibre area were assessed by histological examination. Because the muscle loss and weakness may be related to oxidative stress, 20 we examined both the serum and muscle MDA concentrations ( Figure 6F ); capsaicin and testosterone could effectively decrease the MDA level, showing the ability to modulate oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, alleviated grip strength and the myofibre area were assessed by histological examination. Because the muscle loss and weakness may be related to oxidative stress, 20 we examined both the serum and muscle MDA concentrations ( Figure 6F ); capsaicin and testosterone could effectively decrease the MDA level, showing the ability to modulate oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological targeting or gene knockdown of DUSP22 inhibited signaling by JNK (also known as stress-activated kinase) and FOXO3a (a key regulator of skeletal muscle atrophy). DUSP22 is also known as JNK-stimulating phosphatase 1 (JSP1) and JNK activation has been shown to promote FOXO3a activation in numerous cell types [19][20][21][22]. To confirm the ability of DUSP22 to stimulate JNK in this study, we showed that gene knockdown in skeletal muscle downregulated JNK and the downstream mediator, c-jun.…”
Section: Discussionmentioning
confidence: 67%
“…JNK signaling is increased in cancer-associated skeletal muscle loss and upregulates the atrogenes atrogin-1 (Fbxo32) MuRF-1 (Trim63) and [18]. JNK signaling has been shown to induce the activation of FOXO3a, which is a master regulator of skeletal muscle wasting and transcriptional activator of MuRF-1 and atrogin-1 [19][20][21][22]. Thus, JNK could be a drug target for this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin remains the most intensively studied individual compound [35][36][37][40][41][42][43][44][46][47][48]. Cisplatin suppresses protein synthesis via an Akt protein kinase B (Akt)-dependent mechanism, which leads to p70S6k1 dephosphorylation.…”
Section: Molecular Pathways Of Systemic Treatment-related Muscle Lossmentioning
confidence: 99%